2019
DOI: 10.3389/fchem.2019.00306
|View full text |Cite
|
Sign up to set email alerts
|

Recent Applications of Interfacial Exciplex as Ideal Host of Power-Efficient OLEDs

Abstract: Currently, exploring the applications of intermolecular donor-acceptor exciplex couple as host of OLEDs with phosphorescence, thermally activated delayed fluorescence (TADF) or fluorescence emitter as dopant is a hot topic. Compared to other host strategies, interfacial exciplex has the advantage in various aspects, such as barrier-free charge injection, unimpeded charge transport, and the energy-saving direct exciton formation process at the “Well”-like heterojunction interface region. Most importantly, due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 65 publications
(110 reference statements)
0
18
0
Order By: Relevance
“…More recently, exciplex-forming hosts have also been proposed to achieve barrier-free charge injection, unimpeded charge transport, and more generally as a cost-effective method as exciplexes can be simply formed by physical blending ( Zhang and Xie, 2019 ). Huang et al demonstrated efficient NIR EL by exploiting the energy transfer between the exciplex-forming host blend and the fluorescent guest ( Huang et al., 2020 ).…”
Section: Approaches To Nir Light Generationmentioning
confidence: 99%
“…More recently, exciplex-forming hosts have also been proposed to achieve barrier-free charge injection, unimpeded charge transport, and more generally as a cost-effective method as exciplexes can be simply formed by physical blending ( Zhang and Xie, 2019 ). Huang et al demonstrated efficient NIR EL by exploiting the energy transfer between the exciplex-forming host blend and the fluorescent guest ( Huang et al., 2020 ).…”
Section: Approaches To Nir Light Generationmentioning
confidence: 99%
“…The RISC process can accomplish efficiently through smaller ΔE ST . Owing to the preponderances of low turnon voltage and higher power efficiency, there are more and more reports on TADF exciplex-based WOLEDs recently [125][126][127][128][129][130][131][132].…”
Section: Tadf Exciplexmentioning
confidence: 99%
“…[ 30 ] However, we note that there are few examples of solution‐processed TADF‐OLEDs based on exciplex hosts simultaneously exhibiting low driving voltage and high EQE for achieving high PE. [ 11,31 ]…”
Section: Introductionmentioning
confidence: 99%